2020
DOI: 10.3389/fvets.2020.584673
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus Infection of the Central Nervous System: Animal Models in the Time of COVID-19

Abstract: Naturally occurring coronaviral infections have been studied for several decades in the context of companion and production animals, and central nervous system involvement is a common finding, particularly in cats with feline infectious peritonitis (FIP). These companion and production animal coronaviruses have many similarities to recent human pandemic-associated coronaviruses such as SARS-CoV, MERS-CoV, and SARS-CoV2 (COVID-19). Neurological involvement is being increasingly recognized as an important clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 114 publications
0
5
0
Order By: Relevance
“…The main active ingredient of Mutian X is a nucleic acid analogue with anti-viral effects. Its pharmacokinetic analysis in cats showed that its cerebrospinal fluid concentration was approximately 20% of its plasma levels and that doses five times those shown to effectively treat non-neurologic FIP would be necessary to achieve the drug concentration required to prevent viral cytopathic effects [ 31 ]. The results obtained in our study suggest that the possible spread of FCoV infection to the central nervous tissue, where anti-viral substances may be inadequately distributed, may result in increased disease severity and lower survival rates ( Table 4 and Table 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…The main active ingredient of Mutian X is a nucleic acid analogue with anti-viral effects. Its pharmacokinetic analysis in cats showed that its cerebrospinal fluid concentration was approximately 20% of its plasma levels and that doses five times those shown to effectively treat non-neurologic FIP would be necessary to achieve the drug concentration required to prevent viral cytopathic effects [ 31 ]. The results obtained in our study suggest that the possible spread of FCoV infection to the central nervous tissue, where anti-viral substances may be inadequately distributed, may result in increased disease severity and lower survival rates ( Table 4 and Table 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been confirmed that the anti-FCoV agent GS-441524, MPV, and its activated form N4-hydroxycytidine (EIDD1931) can cross the blood-brain barrier and migrate into the brain after administration into the blood. However, because the transfer efficiency from circulation to intraocular tissues and cranial nerves is not sufficient, it is necessary to increase the dosage to obtain a sufficient amount of the drug [11,31,32]. In our study, we included cases in which the dosage of MPV was increased to a maximum of 20 mg/kg twice a day, depending on the symptoms of each type of FIP; however, higher dosages were not always observed in non-effusive FIP (data not presented).…”
Section: Discussionmentioning
confidence: 99%
“…For rhesus monkeys and SARS-CoV-2, they stated, "no clinical disease reproducible equivalent in severity to human disease" and, for murine models, "brain involvement -not described". Similarly, Dickinson (2020) suggested such studies in October 2020, referring to other coronavirus models, but also cautioned that " [d] (Gomes et al, 2020;Marinho et al, 2021).…”
Section: Brain Organoids Pioneered Knowledge On Sars-cov-2 Brain Infectionmentioning
confidence: 99%